Make a Match Learning for English Conversation Skills of Students with Intellectual Disabilities - Desmiyanti Desmiyanti; Yuanita Yuanita; Kaspul Anwar (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2020)
Background:This research aimed to discover the effectiveness of Make-A-Match model in improving the English conversation skills of students with intellectual disabilities. The participants of this research were 7th-grade students in Class C of SMPLB (Junior High School for Special Needs) JambiMethodology:The data in this applied action research were obtained by using observation, interviews, and notes. This research was conducted in 3 cycles using four steps: planning, acting, observing, and reflecting in each cycle.Findings:The result showed that using the contextual approach to Make-A-Match model was sufficient to improve English conversation skills of students with intellectual disabilities. The students were more active, enthusiastic, and confident in uttering expressions without being anxious about making mistakes because the classroom atmosphere was relaxing and fun. This model also made students worked well together.Conclusion:through this model, the teacher succeeds in encouraging students to apply English in their daily conversation.